Micro and Nanoplastics Identification: Classic Methods and Innovative Detection Techniques - Mariano, Stefania; Tacconi, Stefano; Fidaleo, Marco; Rossi, Marco; Dini, Luciana (Frontiers in Toxicology, 2021)
Micro and nanoplastics are fragments with dimensions less than a millimeter invading all terrestrial and marine environments. They have become a major global environmental issue in recent decades and, indeed, recent scientific studies have highlighted the presence of these fragments all over the world even in environments that were thought to be unspoiled. Analysis of micro/nanoplastics in isolated samples from abiotic and biotic environmental matrices has become increasingly common. Hence, the need to find valid techniques to identify these micro and nano-sized particles. In this review, we discuss the current and potential identification methods used in microplastic analyses along with their advantages and limitations. We discuss the most suitable techniques currently available, from physical to chemical ones, as well as the challenges to enhance the existing methods and develop new ones. Microscopical techniques (i.e. dissect, polarized, fluorescence, scanning electron, atomic force microscopy) are one of the most used identification methods for micro/nanoplastics, but they have the limitation to produce incomplete results in analyses of small particles. At present, the combination with chemical analysis (i.e. spectroscopy) allows this limit to be overcome. Moreover, recent studies introduced other approaches thus improving this research area. For example, holographic imaging in microscope configuration has been used to image microplastics directly in unfiltered water, demonstrating the ability to recognize microplastics, to discriminate them from diatoms and to differentiate between different sizes, shapes, and plastic types. The development of new analytical instruments coupled with one another or with conventional and innovative microscopies could solve the current problems in micro/nanoplastics identification.